A Showcase of Authentic Learning Activities in an EFL Class - Santoso, Martha Nandari (Beyond Words, 2018)
One of the major constraints of the teaching of English as a foreign language (EFL) is the deficient opportunities to apply the lessons students learn in the classroom in a meaningful context. Students may have a lot of knowledge about the language but may not be able to apply the knowledge in real life communication. Students who study EFL in conventional classrooms will suffer the most. This paper discusses a practical framework for teachers of EFL who would like to alter their traditional classes, which mostly happen in the classroom, to authentic learning activities or activities that promote real-life applications of knowledge, which happen in real-world situations. I showcased in detail the implementation of the framework in one EFL course at the English Education Program of a private university in Indonesia. I also discussed the drawbacks, possible solutions as well as the pedagogical implications with some students’ excerpts of their reflections toward the activities to support the discussion.